Quorum sensing inhibition and antibacterial activity of plany extracts separation and profiling of bioactive compounds - Resano, Mia Keen P.
The richness of bioactive compounds in plants encourages continuous development of separation methods and bioassays for their isolation and identification. Thin layer chromatography (TLC) bioautography allows the separation of bioactive compounds from plant extracts and simultaneous determination of its biological activity. Aqueous-dispersed methanolic extracts of Halymenia durvillei (Bory de Saint-Vincent), Coleus aromaticus (Oregano), Moringa oleifera (Malunggay), and Curcuma longa (Turmeric) were screened for antibacterial activity against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa, and quorum sensing inhibition against Chromobacterium violaceum ATCC 12472. Hence, antibacterial and QSI active fractions were detected. H. durvillei and C. longa were found to have the most potent antibacterial activity. QSI of both extracts showed that they inhibited the violacein production of C. violaceum at 50% v/v (0.5 g/mL) and 75% (0.75 g/mL), respectively. TLC of C. longa using chloroform: methanol (95:5) as the mobile phase showed three bandswidth R_f values of 0.27, 0.54, and 0.80, respectively. Bioautography of the profile revealed that the band at R_f=0.80 exhibited antibacterial activity against E. coli and S. aureus, and also showed QSI against C. violaceum. TLC of H. durvillei with dichloromethane: ethyl acetate (9:0.9) yielded three bandswidth R_f values of 0.80, 0.89, and 0.97, respectively. Bioautography of the profile for antibacterial activity revealed that there was no inhibition from any of the bands. Thus, synergistic effects could be presumed. Bioautography of the profile against C. violaceum indicated which band possesses QSI activity. The compound may be associated to one of the secondary metabolites present in the plant that has the capability to mimic AHL signaling molecules of C. violaceum.